(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Food has always been a big deal in ethnic cultures. Assam is a state in north-eastern India that is diverse and rich in culture. It is a region where many different tribes coexist. Each tribe maintained its indigenous ethnicity in addition to its eating practices. The tradition of preparing alcoholic beverages is considered to be essential to certain tribal rituals. This study mostly focused on the following tribes: Ahom, Bodo, Deori, Missing, Rabhas, Karbis, Dimasa, and SonowalKacharis. The way that alcohol is used and how it is prepared, as well as the names of these traditional drinks are vary from tribe to tribe. The observation and descriptive approaches are used in this work to explore the drinking cultures of these Assamese tribes. The human mind’s curiosity about regional beverages never goes away with time. Drinking traditional beverages and experimenting with them not only offers a specific honour to cultural heritage but also enhances flavour.